ANALISIS EFEKTIFITAS PENGGUNAAN CADANGAN DEVISA DAN FINANCIAL DEEPENING TERHADAP STABILITAS NILAI TUKAR - Muhammad Aulia; Raja Masbar (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2016)
This research aims to analyse the impact of international reserve and financial deepening on exchange rate stability and to analyze the effectivity of international reserve and financial deepening as exchange rate stabilizer. Vector Error Corection Model (VECM) were used in this research with quarterly data from year 2002:01 to 2015: 04. The result showed that international reserve and financial deeepening have effect on exchange rate. Based on Impulse Response Function (IRF), financial deepening variable is more effective used to stabilise the exchange rate fluctuation because it influences investment which that national output and export. For the further research, it is recommended as in order to capture the negative effect and to the use of the respective variables as an exchange rate stabilizer.